Volume 10: Petroleum Technology 2022
DOI: 10.1115/omae2022-79074
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Understanding the Potential of Enhanced Oil Recovery for a Candidate Offshore Sandstone Field

Abstract: The aim of this investigation is to develop a comprehensive understanding of an enhanced oil recovery (EOR) candidate reservoir based in an unconventional sandstone dominated environment. The unique geology, owing to its proximity to an inland, endorheic basin, alongside its complex stratigraphic geometry incorporating extensive folding and faulting as well as a laterally extensive unconformity. The study leans heavily on the forefront of reservoir characterizations. Reservoir characterization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The geological background and reservoir characterization of the targeted field have been well summarized by Qi et al 18 and Rabbani et al 19 Based on field data, representative core plugs cut from Gray Berea sandstone outcrops were chosen for the polymer core-flood experiments. Sixteen core plugs (batch 1) were used for the formation damage test, and 10 core plugs (batch 2) were used for the polymer core-flood oil displacement efficiency study.…”
Section: Methodsmentioning
confidence: 99%
“…The geological background and reservoir characterization of the targeted field have been well summarized by Qi et al 18 and Rabbani et al 19 Based on field data, representative core plugs cut from Gray Berea sandstone outcrops were chosen for the polymer core-flood experiments. Sixteen core plugs (batch 1) were used for the formation damage test, and 10 core plugs (batch 2) were used for the polymer core-flood oil displacement efficiency study.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, oil fields with complex geological structure have been discovered in many oil and gas bearing regions of the world [1,2]. These fields are characterized by low oil saturated thickness of reservoirs, low filtration-capacity properties of reservoirs, high viscosity of reservoir oil and heterogeneity of productive horizons, etc [3].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important issues in increasing the degree of oil recovery from the subsurface is the study of structural and mechanical properties of polymer solutions, their influence on the filtration process in the reservoir and ways to regulate them. At present, a large amount of theoretical and experimental material has been accumulated to study the structural and mechanical properties and flow characteristics of non-Newtonian oils [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Studies have shown that during the development of wells that have opened deposits of heavy high-viscosity oils, there are complications associated with the difficulty of lifting oil to the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation